2012
DOI: 10.1128/aac.01739-12
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Staphylococcus epidermidis Biofilm by Trimethylsilane Plasma Coating

Abstract: c Biofilm formation on implantable medical devices is a major impediment to the treatment of nosocomial infections and promotes local progressive tissue destruction. Staphylococcus epidermidis infections are the leading cause of biofilm formation on indwelling devices. Bacteria in biofilms are highly resistant to antibiotic treatment, which in combination with the increasing prevalence of antibiotic resistance among human pathogens further complicates treatment of biofilm-related device infections. We have dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 106 publications
3
52
0
Order By: Relevance
“…A surface with antibacterial properties, high capacity for cell attachment and able to release biological factors could be an effective way to avoid bacteria adhesion and improve osseointegration. Previous studies had suggested that different silanes could affect osteoblasts [8] or present antibacterial activity on steel, Ti6Al4V or glass [9,10]. This study tested in vitro the hypothesis that titanium coated with TESPSA silane has antibacterial properties while inducing osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A surface with antibacterial properties, high capacity for cell attachment and able to release biological factors could be an effective way to avoid bacteria adhesion and improve osseointegration. Previous studies had suggested that different silanes could affect osteoblasts [8] or present antibacterial activity on steel, Ti6Al4V or glass [9,10]. This study tested in vitro the hypothesis that titanium coated with TESPSA silane has antibacterial properties while inducing osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 93%
“…In the case of silanization, silane molecules act as a binder between the substrate and the biomolecules. This technique could be improved using silanes that elicit specific cell responses, such as proliferation, differentiation [8] or antibacterial effects [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Data suggest that inhibition of biofilm formation within a short period in a the infection early phase could be beneficial [49].…”
Section: Biofilm and Bacterial Advantagesmentioning
confidence: 99%
“…When the antitoxin is degraded an imbalance occurs in this system, leading to activation of the toxin inducing a bacteriostatic effect [48]. It is clear that the exchange of genetic material among bacterial strains contributes to the emergence of resistance and plays a key role in the persistence of biofilms-associated infections [49].…”
Section: Biofilm and Bacteriamentioning
confidence: 99%
See 1 more Smart Citation